Keabsahan Peralihan Harta Warisan Berdasarkan Surat Keterangan Wasiat - Jimmy Joseph; Jenny Kristiana Matuankotta; Mahrita Aprilya Lakburlawal (PATTIMURA Law Study Review, 2023)
The position of the heirs in the distribution of inheritance based on a testamentary certificate must be in accordance with the position of the heirs based on the law and the will, so the heirs are only those from the family who have the closest blood relationship to the heirs according to the law. Relating to the consequences of a legal action or event that can have legal consequences for that person or other people. In relation to his will, the legal effect on the heirs is that the testament made by Mrs. SS as intended in this writing can result in being null and void because because it is not valid it cannot apply. A testamentary statement cannot be called a will because it was not made before or entrusted to a notary as regulated in the Civil Code. So that the transfer of inherited assets from the heir to the heirs is an inheritance according to law or ab intestato inheritance. This research method is a descriptive normative legal research method. Which consists of research types, the problem approach taken is a statutory approach and a conceptual approach, legal materials consisting of primary legal materials, secondary legal materials and tertiary legal materials, procedures for collecting legal materials, and finally processing and analysis of legal materials. The results of the research show that the certificate of will made by the testator in terms of the definition of a will in Article 875 of the Civil Code and interviews with notaries regarding the meaning of a certificate of will have the same purpose in that they both explain the will of someone who will die, however The difference is that a will or testament is a deed if it is defined as a document made in accordance with the provisions regulated by law, by or in the presence of an authorized public official at the place where the deed is made. Thus, the certificate of will as referred to in this case is not a will because it was not made by and/or in the presence of an official, it was made by the testator and heirs, so it cannot be called a will. A testamentary statement made by the testator cannot be said to be a will or invalid. So the legal consequence in the case that has been explained is that the certificate of will is null and void, he does not exist because based on the certificate of will made by the heir some of the heirs did not receive their share or right to inherit.